Relationship between suicidal patients and vitamin D: A prospective case-control study - Atik, Dilek; Cander, Basar; Dogan, Serkan; Bulut, Bensu; Yazıcı, Ramiz; Taslidere, Bahadir (Journal of Surgery and Medicine, 2020)
Aim: When a person ends their life consciously and intentionally, it is called suicide. One of the most investigated issues related to suicide is mental disorders. It has been reported that vitamin D has a prominent role in the treatment of many chronic diseases in recent years. Growing evidence implicates sunlight, or vitamin D, is a key environmental factor in the etiology of neuropsychiatric diseases. The aim of this study was to investigate the vitamin D levels in patients admitted to our emergency department due to suicide intervention and contribute to the treatment of clinical applications according to the results. Methods: This study included 59 individuals with suicidal attempt and 42 control group subjects. The gender, age, educational level, marital status, and economic status of the patients, whether they had previously received psychiatric treatment, or attempted suicide were recorded in a separate Sociodemographic Information Form (SBF) for each patient. Mann Whitney U test was used for statistical evaluations based on categorical (nominal or ordinal) and binary variables. Results: The minimum and maximum Vitamin D laboratory parameters of the study group were 4.4 ng/ml and 33 ng/ml, respectively. The mean vitamin D levels in the suicide and control groups were 9.6 ng/ml and 13.8 ng/ml, respectively. There were statistically significant relationships between vitamin D levels, the presence of psychiatric disease (P<0.001) and previous suicide attempts (P=0.02). Conclusion: Suicidal tendency increases in depression, which is a psychiatric illness. We believe that suicide attempts may be reduced by adding vitamin D to treatment protocols, especially in depression, and that it may direct future studies in this direction.